2014
DOI: 10.1016/j.neuroscience.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Two functional inhibitory circuits are comprised of a heterogeneous population of fast-spiking cortical interneurons

Abstract: Cortical fast spiking (FS) interneurons possess autaptic, synaptic, and electrical synapses that serve to mediate a fast, coordinated response to their postsynaptic targets. While FS interneurons are known to participate in numerous and diverse actions, functional subgroupings within this multi-functional interneuron class remain to be identified. In the present study, we examined parvalbumin positive FS interneurons in layer 4 of the primary somatosensory (barrel) cortex - a brain region well-known for specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…All slices were incubated at 32°C for one hour prior to recording at room temperature. We followed previously described methods for obtaining electrophysiological parameters for active and passive membrane properties including input resistance, resting membrane potential, capacitance, Rheobase, action potential threshold, amplitude and frequency (Li and Huntsman, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All slices were incubated at 32°C for one hour prior to recording at room temperature. We followed previously described methods for obtaining electrophysiological parameters for active and passive membrane properties including input resistance, resting membrane potential, capacitance, Rheobase, action potential threshold, amplitude and frequency (Li and Huntsman, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Biocytin-filled neurons were further processed as previously described (Li and Huntsman, 2014). Images were obtained by confocal microscopy (FluoView, Olympus).…”
Section: Methodsmentioning
confidence: 99%
“…Axonal arborization of most FS-PV cells is usually confined to the home-barrel, with the exception of minor populations of basket cells (Koelbl et al, 2015;Li and Huntsman, 2014;Rudy et al, 2011;Shigematsu et al, 2018). To explore whether such spatial pattern of functional projections of developing PV cells was also affected by MIA or embryonic microglial depletion, we used PV cre/+ ;R26 Chr2/+ mice, and measured the inhibitory drive evoked by a local optogenetic activation of PV interneurons on single principal cells belonging to the same vs neighboring barrels (Figure 3A-F).…”
Section: Miswiring In Juveniles Impairs Propagation Of Sensory Informmentioning
confidence: 99%
“…Such spiking behavior strongly resembles that of the gnsFS described here in SI. Li and Huntsman (2014) reported two broad electrophysiological categories of FS within layer 4 of SI barrel cortex based on the onset of the first action potential in a depolarizing train. They found that FS that showed delayed spiking in response to current injection also had smaller thalamocortical-evoked responses compared to early spiking FS, potentially reflecting the sensory and non-sensory subtypes observed in the present study.…”
Section: Discussionmentioning
confidence: 99%